The pathobiology of myalgic encephalomyelitis/chronic fatigue syndrome: the case for neuroglial failure - Renz-Polster, Herbert; Tremblay, Marie-Ève; Bienzle, Dorothee; Fischer, Joachim E. (Frontiers in cellular neuroscience, 2022)
Although myalgic encephalomyelitis/chronic fatigue syndrome (ME/CFS) has a specific and distinctive profile of clinical features, the disease remains an enigma because causal explanation of its pathobiological matrix is lacking. Several potential disease mechanisms have been identified, including immune abnormalities, inflammatory activation, mitochondrial alterations, endothelial and muscular disturbances, cardiovascular anomalies, and dysfunction of the peripheral and central nervous systems. Yet, it remains unclear whether and how these pathways may be related and orchestrated. Here we explore the hypothesis that a common denominator of the pathobiological processes in ME/CFS may be central nervous system dysfunction due to impaired or pathologically reactive neuroglia (astrocytes, microglia and oligodendrocytes). We will test this hypothesis by reviewing, in reference to the current literature, the two most salient and undisputed features of ME/CFS, and by investigating how these might be linked to dysfunctional neuroglia. From this Review we suggest that the multifaceted pathobiology of ME/CFS could be attributed in a unifying manner to neuroglial dysfunction. Because the two features - post exertional malaise and decreased cerebral blood flow - are now also recognized as central hallmarks in a subset of post-acute sequelae COVID-19 patients, we suggest that our findings may extend to this entity, too.